From Coordination Polyhedra to Molecular Environment and Back – Interplay between Coordinate and Hydrogen Bonds in Two Polymorphs of a Cobalt Complex. Issue 13 (4th April 2013) - Ananyev, Ivan V.; Nefedov, Sergey E.; Lyssenko, Konstantin A.
Abstract: Two crystalline modifications of a cobalt(II) benzoate complex containing substituted pyrazole ligands are investigated. The polymorphs are characterized by different intermolecular bonding as well as by different metal‐atom environments. A thorough analysis of the chemical bonding patterns by means of Bader's "Atoms in Molecules" theory reveals the significant role of N–H··· O hydrogen bonds in charge transfer within the molecule and in stabilization of unfavorable [4+1] cobalt polyhedra. Specifically, an estimation of the interaction energies according to an Espinosa correlation scheme shows the significant contribution of H bonds to the stabilization energy of the molecular conformations. Abstract : A thorough analysis of the chemical bonding patterns in two polymorphs of a cobalt(II) benzoate complex with substituted pyrazole ligands by using Bader's "Atoms in Molecules" theory reveals the crucial role of N–H··· O hydrogen bonds in the stabilization of unfavorable [4+1] cobalt polyhedron.